Beyond the spiral of hate: Reconstructing positive memory - Blagojević Marina (Temida)
(Re) construction of positive memory should provide deconstruction of existing, ruling paradigms about Balkan as the space predestinated for "repeating the history" and eternal antagonisms between different ethnic groups. In this way, the basis will be created for establishment of a new paradigm for understanding of the wars in the former Yugoslavia and elsewhere. Also, the process of reconciliation will be strengthened and the sense of our own individual and collective responsibility for "good" instead of "bad" "destiny" will be developed. "Positive history" is necessary element of both self-understanding and the process of creation of individual, collective and regional identity. It is also necessary element for understanding of THE CONTINUUM OF THE GOODNESS, as well as of imperishability of the need for the exchange and cooperation, and therefore for reconciliation and reconstruction.